‘One World - One Health’ and the global challenge of epidemic diseases of viral aetiology - E. Paul J. Gibbs, BVSc, PhD, FRCVS; Tara C. Anderson, DVM, MPH (Veterinaria Italiana, 2009)
‘One World - One Health’ is an exciting movement to encourage wildlife, domestic animal and human health professionals to work collectively to address the world’s most challenging health concerns. It is broad in scope and truly multidisciplinary. This particular commentary on ‘One World - One Health’ is focused on ways in which individuals are forging closer collaboration and action to meet the global threat of emerging diseases caused by viruses, with particular attention being paid to those diseases that are zoonotic.